Knowledge of First Aid Road Traffic Accident Victim Among Police Officers in Banjarmasin - Trifianingsih, Dyah; Warjiman; Nirwani Agri (STIKES Suaka Insan, 2024)
Traffic accidents can lead to medical emergencies that threaten the health and safety of victims. Immediate, appropriate treatment is crucial to minimize severe bodily harm, disability, or death. Traffic police, as first responders at the scene, can provide critical first aid before professional medical personnel arrive, relying on their adequate knowledge and skills. This study aims to assess the knowledge of traffic police in providing first aid to accident victims. This quantitative descriptive study was conducted on 83 traffic police officers in Banjarmasin, selected using total sampling. Data were collected through questionnaires, and the analysis was carried out using frequency distribution. Among the 83 respondents, 61 (73%) had sufficient knowledge, 18 (22%) had good knowledge, and 8 (5%) had poor knowledge. These findings highlight the need for educational interventions to improve the respondents' knowledge in providing first aid during traffic accidents.